2011
DOI: 10.1097/aln.0b013e3182217126
|View full text |Cite
|
Sign up to set email alerts
|

Human Subthalamic Neuron Spiking Exhibits Subtle Responses to Sedatives

Abstract: Background: During deep brain stimulation implant surgery, microelectrode recordings are used to map the location of targeted neurons. The effects produced by propofol or remifentanil on discharge activity of subthalamic neurons were studied intraoperatively to determine whether they alter neuronal activity. Methods: Microelectrode recordings from 11 neurons, each from individual patients, were discriminated and analyzed before and after administration of either propofol or remifentanil. Subthalamic neurons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
3
22
3
Order By: Relevance
“…In this study, we found that the continuous infusion of propofol and fentanyl did not significantly interfere with the mean firing rates of the STN in comparison with awake monitoring in the same patient and showed good clinical outcomes comparable to a previous report (7). The results of the mean firing rates in both awake and MAC conditions are similar to some previous reports ranging between 33.1 Hz and 42.3 Hz (3, 19, 20, 21, 22, 23, 24, 25). These results imply that the MAC has just minimal effects on the firing rate of STN neurons in PD patients.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that the continuous infusion of propofol and fentanyl did not significantly interfere with the mean firing rates of the STN in comparison with awake monitoring in the same patient and showed good clinical outcomes comparable to a previous report (7). The results of the mean firing rates in both awake and MAC conditions are similar to some previous reports ranging between 33.1 Hz and 42.3 Hz (3, 19, 20, 21, 22, 23, 24, 25). These results imply that the MAC has just minimal effects on the firing rate of STN neurons in PD patients.…”
Section: Discussionsupporting
confidence: 90%
“…A critical limitation in our understanding of anesthetic best practices is that only a few studies have quantified the effect of anesthetics on MER [14,41,44,45], although a number have qualitatively assayed it, suggesting that too much sedation degrades the MER quality [13,14,15,20,39,41,42,43,44,46,47,48,49,50,51,52,53,54]. Considering those studies that quantified the effects on MER, we do know that some were affected by anesthetic choice, for example, during propofol sedation, background population activity within the STN, as well as FR, was reduced [13,14,41,43,44,51], REMI combined with ketamine demonstrated a reduction in background activity with preserved neuronal FRs [45], and REMI alone had no effect [41]. This study, combined with the results of the study by Krishna el al.…”
Section: Discussionmentioning
confidence: 99%
“…At the doses employed during our routine care, patients are functionally free of the REMI during the MER and neurological assessment portion of the procedure and, hence, for the purposes of this study served as a suitable (and practical) active control for the effects of DEX [41]. Consistent with this, our data are strikingly similar to a recent retrospective study in which single unit measures and local field potentials were compared between patients who received DEX during recording versus no sedative agents [21].…”
Section: Discussionmentioning
confidence: 99%
“…These effects can be detected in the neural recording as an underlying low frequency change in the amplitude of the noise. This contaminant should be considered during spike sorting and appropriate methods for waveform detection should be applied, as this underlying oscillation will change the amplitude of recorded action potentials 27,28 . In addition, this type of recording session generally results in poor signal quality and stability.…”
Section: |mentioning
confidence: 99%